Effect of Water pH on the Efficiency of Eggshells in Removing Cr (VI) Ion from Water - Elbahi , Samia A. (Al-Mukhtar Journal of Sciences, 2022)
Recently, various types of bio-adsorbents of animal or vegetable sources with minimal cost and less effort, which are obtained from domestic and agricultural waste, have been explored. In the present work, the possibility of using chicken eggshell powder as an adsorbent material to remove hexa-chromium metal from an aqueous solution was studied. Calcium carbonate, magnesium carbonate, and calcium phosphate are the primary components of eggshell powder, which in turn have a substantial and effective role in the adsorption process. In this study, 6 g of adsorbent (egg shells) was mixed with 3 mg of hexa-chromium per liter of pure water solution at a temperature of (40) °C and within the pH range (3, 6, 9). It was found that calcified eggshells have the ability to adsorb hexa-chromium ions, with a removal rate of 88.767% at pH 6 within 60 minutes.